96.5k views
0 votes
Find (f −1)(a)

f(x) = 3x^3 + 3x^2 + 6x + 5, a = 5

1 Answer

3 votes

Answer:

(f −1)(a)= -5

Explanation:

From the problem statement, let us say that you were meant to write

f(-1)a so that x= -1

Moving forward this question requires that we substitute the value of x= -1 in the given equation and multiply the final answer by a which 5


f(x) = 3x^3 + 3x^2 + 6x + 5 \\ f(-1)\\a = 5

Substituting x=-1 for x in the expression we have


f(-1) = 3(-1)^3 + 3(-1)^2 + 6(-1) + 5\\\\f(-1)= 3(-1)+3(1)-6+5\\\\f(-1)= -3+3-6+5\\\\f(-1)= -1\\\\f(-1)a= -1*5\\f(-1)a= -5

User Inoperable
by
6.1k points